FEATURES OF THE PHYSICS TEACHING PROCES - Sultonov Ravshanbek Rustamovich (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article aims to provide methodological assistance to students in teaching and learning physics in secondary schools based on a psychological approach and science based on the laws of nature.